Public Investment and Its Impact on Poverty Systematic Literature Review - Talledo, Luis Rubén Castillo; Huamán , Anthony Carmen; Sánchez, Lorena Beatriz Tume; Rodríguez, Marcos Alejandro Yánez (Journal of Ecohumanism, 2024)
This article presents a systematic review that examines the relationship between public investment and its incidence on poverty at the international and national level, (Peru), specifically in the El Carmen de la Frontera district, Huancabamba. The PRISMA method was used and an exhaustive analysis of various academic sources such as Scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex and the César Vallejo University was carried out, in which it was identified that public investment, especially in sectors such as health, education and infrastructure, has a positive impact on poverty reduction and economic development. However, despite increases in public spending, the results show that poverty rates have not decreased uniformly, highlighting the need to improve the efficiency and effectiveness of investments. The review also highlights socioeconomic factors that moderate this relationship and shows regional disparities in the impact of public investment. It is concluded that adequate management and strategic planning are essential to maximize the benefits of public investment and contribute to sustainable human development.